Pengembangan Model Pengolahan Tongkol Jagung dalam Meningkatkan Kualitas Tanah dan Lahan Kritis Melalui Produksi Biochar dan Cuka Kayu di Desa Waji, Kecamatan Tellu Siattinge, Kabupaten Bone, Provinsi Sulawesi Selatan - Agus Salim, Sakila; Salim, Sakila Agus (Universitas Hasanuddin, 2025)
Appropriate Technology Innovation (ITTG) in the form of pyrolysis drum technology has been implemented in Kacumpureng Hamlet, Waji Village, Tellu Siattinge District, Bone Regency, South Sulawesi. This technology consists of a combustion drum to produce biochar and a condensation drum to produce wood vinegar, both of which are produced from processing corncob waste. The development of this technology responds to the abundance of corn cob waste in the area, considering that corn is the leading commodity of the local community. The production process uses an anaerobic combustion method, where corn cobs are burned in minimal oxygen conditions to produce biochar, while the resulting smoke is condensed into wood vinegar. This program is a collaboration between the hamlet head, the Kacumpureng 1 farmer group, and the local community, which includes demonstration activities, operational training, and question and answer sessions. The aim is to empower communities to utilize agricultural waste, improve soil quality through the use of biochar, reduce dependence on chemical fertilizers, and contribute to reducing the impact of global warming. Through this program, it is hoped that the community can optimize the use of natural resources while preserving the environment.